Self-Efficacy Correlated with Diarrhea Prevention Behaviors - Jeni Moudy Pujianti; Cory Nelia Damayanti; Mujib Hannan (Journal of Ners and Midwifery, 2023)
Diarrhea is a gastrointestinal disease with extraordinary events (KLB) that requires special attention because the high morbidity and death rates are still a health problem for people worldwide, especially in developing countries like Indonesia. It happens because of the low correlation of self-efficacy in implementing diarrhea prevention behaviors. This research aimed to determine the correlation between self-efficacy and diarrhea prevention behavior in the work area of Kalianget Health Center. The type of the research was quantitative with an analytical observational design with a cross-sectional approach. The population was 217 respondents suffering from Diarrhea and the sample was 67 respondents taken by simple random sampling. The data collection used questionnaires. Test analysis using Spearmen rank test. This research showed that as many as 47 respondents (70.1%) had a moderate level of Self-efficacy, while most respondents had behavior Diarrhea prevention in the sufficient category 48 respondents (71.6%). Analysis of the data obtained there was a correlation between self-efficacy and preventive behavior Diarrhea in the working area of Kalianget Health Center. Prevention of Diarrhea in people with Diarrhea can be done by increasing self-efficacy so that diarrhea prevention behavior can be carried out properly and correctly to reduce the incidence of Diarrhea in the community